Assessing the Drought Years for Rainfall Data through Precipitation Index-Rainfall Anomaly Index - Rani, Seedari Ujwala; Kishore, Modem Ravi; Sunanda, N.; Appalaswamy, A.; Rani, N. Sri Vidya (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
The climate indices of the Rainfall Anomaly Index and mean deviation methods are used to identify drought years and wet years over both spatial and temporal on the time scale. The rainfall data from 1979-2019 was collected from CRIDA, Hyderabad for the hilly Zone in Karnataka state in India. In Hilly Zone, the dry years occurred for 19 years. Extreme drought occurred in 2016, 2001, 2002, 2015, 2003, 1987 and 2017 (< -3 RAI). With climate issues high on the global agenda, the potential role of efficient water management in drought-affected areas in climate change adaptation is attracting widespread attention among state and national governments. RAI is used to assess and identify droughts, drought severity and variability by comparing with some established arbitrary value.